1989
DOI: 10.1002/anr.1780320520
|View full text |Cite
|
Sign up to set email alerts
|

Therapy for systemic juvenile rheumatoid arthritis with γ‐interferon: A pilot study of nine patients

Abstract: Nine severely ill patients with a confirmed diagnosis of systemic juvenile rheumatoid arthritis were treated with recombinant y-interferon (y-IFN) in addition to the therapy they were previously receiving for their disease. Improvements in clinical symptoms were noted in 7 of the patients, and median laboratory values also showed a marked improvement after y-IFN treatment. A relapse occurred in 1 patient. The results of this study should stimulate further research on the use of y-IFN in systemic juvenile rheum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Due to this finding, a placebocontrolled double-blind study with gamma interferon in adults with rheumatoid arthritis was undertaken. 65 The results of the study showed a 58% response to the treatment. Since then, gamma interferon has been studied as a pilot trial in 9 pediatric patients with systemic onset JRA.…”
Section: Miscellaneous Therapiesmentioning
confidence: 85%
See 2 more Smart Citations
“…Due to this finding, a placebocontrolled double-blind study with gamma interferon in adults with rheumatoid arthritis was undertaken. 65 The results of the study showed a 58% response to the treatment. Since then, gamma interferon has been studied as a pilot trial in 9 pediatric patients with systemic onset JRA.…”
Section: Miscellaneous Therapiesmentioning
confidence: 85%
“…Findings in an adult population with rheumatoid arthritis have shown that gamma interferon is diminished by leukocytes in vitro. 65 Additional research has shown the effectiveness over time with gamma interferon in the treatment of adult RA when dosage decreases are made. Due to this finding, a placebocontrolled double-blind study with gamma interferon in adults with rheumatoid arthritis was undertaken.…”
Section: Miscellaneous Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-β and IFN-γ down-regulate pro-inflammatory cytokine and up-regulate anti-inflammatory cytokine production and may thus have potential as a therapy for RA. [151,152] Most of the studies were double-blind and placebo-controlled, and were small, each with <50 patients.…”
Section: Interferon (Ifn)-γ and Ifn-βmentioning
confidence: 99%
“…For example, ,y-IFN has already been used with varying success as a therapeutic agent in the treatment of rheumatoid arthritis in both adults and children [62]. In large double-blind clinical trials, results have generally been indeterminate [63].…”
Section: Drugs and Cytokinesmentioning
confidence: 99%